Aplikasi Kebugaran Defense In Depth Untuk Aplikasi Kebugaran Perusahaan Start-Up Menggunakan Microsoft Azure - Holilah Holilah; Husyen Ali Alhabsy; Tb. Muhammad Farhan Adnan; Voully Abdullah Zhacque; Royan Habibie Sukarna; Mohamad Hilman; Andi Moch Januriana (Teknik Informatika Fakultas Ilmu Komputer, 2025)
A start-up company in the fitness and health sector has developed an innovative virtual training platform. The platform allows users to take live fitness classes via their computer, tablet or smartphone, leveraging artificial intelligence (AI) and high-quality video streaming for an interactive and personalized training experience. The platform consists of three main components: the frontend layer (web and mobile applications), the backend layer (application servers), and the data storage layer (cloud database). As the popularity of these platforms increases, companies face challenges in managing on-premises resources, ensuring data security, and complying with strict data protection regulations. This research aims to design a comprehensive cyber security strategy by utilizing Microsoft Azure services to overcome these challenges. This strategy includes identity and access management, data encryption, threat detection and response, and regulatory compliance.